2019
DOI: 10.1093/mnras/stz3235
|View full text |Cite
|
Sign up to set email alerts
|

Periodic transit timing variations and refined system parameters of the exoplanet XO-6b

Abstract: Only a few exoplanets are known to orbit around fast rotating stars. One of them is XO-6b, which orbits an F5V-type star. Shortly after the discovery, we started multicolor photometric and radial-velocity follow-up observations of XO-6b, using the telescopes of Astronomical Institute of the Slovak Academy of Sciences. Our main scientific goals were to better characterize the planetary system and to search for transit timing variations. We refined several planetary and orbital parameters. Based on our measureme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 53 publications
1
14
1
Order By: Relevance
“…Notably, we did not find any evidence of transit timing variations in the case of XO-6b, despite the TESS data having sufficient precision and time baseline to clearly reveal the TTVs reported by Garai et al (2020). Specifically, the 3σ upper-limit on TTVs allowed by the TESS 10 https://github.com/pavolgaj/OCFit observations is 2.5 minutes, while their LiTE model predicts TTVs of 12-14 minutes in Sectors 19 and 20 and 5-9 minutes in Sector 26.…”
Section: Resultscontrasting
confidence: 64%
See 4 more Smart Citations
“…Notably, we did not find any evidence of transit timing variations in the case of XO-6b, despite the TESS data having sufficient precision and time baseline to clearly reveal the TTVs reported by Garai et al (2020). Specifically, the 3σ upper-limit on TTVs allowed by the TESS 10 https://github.com/pavolgaj/OCFit observations is 2.5 minutes, while their LiTE model predicts TTVs of 12-14 minutes in Sectors 19 and 20 and 5-9 minutes in Sector 26.…”
Section: Resultscontrasting
confidence: 64%
“…The analysis of Garai et al (2020) utilized 15 transits, of which 8 were observed by the authors themselves with telescopes at the Astronomical Institute of the Slovak Academy of Sciences and 7 were adopted from the ETD after having been observed by others. While the data obtained from the ETD do not exhibit stronger TTVs than their own observations (see Figure 8 in Appendix D) and they only used data from the ETD that had clearly indicated timing epochs (either JD or HJD) and good quality, it is still possible these data points introduced unaccounted for uncertainties that contributed to the discrepancy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations